2018
DOI: 10.1002/cssc.201702411
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrodeoxygenation of Alkyl Lactates to Alkyl Propionates with Fe‐based Bimetallic Supported Catalysts

Abstract: Hydrodeoxygenation (HDO) of methyl lactate (ML) to methyl propionate (MP) was performed with various base-metal supported catalysts. A high yield of 77 % MP was obtained with bimetallic Fe-Ni/ZrO in methanol at 220 °C and 50 bar H . A synergistic effect of Ni increased the yield of MP significantly when using Fe-Ni/ZrO instead of Fe/ZrO alone. Moreover, the ZrO support contributed to improve the yield as a phase transition of ZrO from tetragonal to monoclinic occurred after metal doping giving rise to fine dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The reduction peaks showed are attributed to the reduction of nickel oxide to zero Valente nickel. Such a result was also noticed by Zhou et al, 34 Khokarale et al, 35 Zafeiropoulos et al, and Guilera et al 37 They have reported that the low-temperature TPR peak is attributed to the highly dispersed surface metal oxide species, and high-temperature TPR peak is attributed to the bulk metal oxide, with no reduction peak for ZrO 2 support.…”
Section: Composite Characterizationsupporting
confidence: 72%
See 1 more Smart Citation
“…The reduction peaks showed are attributed to the reduction of nickel oxide to zero Valente nickel. Such a result was also noticed by Zhou et al, 34 Khokarale et al, 35 Zafeiropoulos et al, and Guilera et al 37 They have reported that the low-temperature TPR peak is attributed to the highly dispersed surface metal oxide species, and high-temperature TPR peak is attributed to the bulk metal oxide, with no reduction peak for ZrO 2 support.…”
Section: Composite Characterizationsupporting
confidence: 72%
“…Ni/ZrO 2 , 2.5La–Ni/ZrO 2 , and 5La–Ni/ZrO 2 catalysts exhibit a single reduction peak referring to more uniform NiO nanocrystals and expose that a reduction temperature at about 400°C is sufficient for complete reduction of the Ni phase in the case of Ni/ZrO 2 catalyst, whereas it increased to 430°C for x La–Ni/ZrO 2 catalysts, assigned to the reduction of the strong support interacting NiO 35 . The H2‐TPR profile of Ni/2.5La–ZrO 2 catalyst showed five reduction peaks at 264°C, 342°C, 372°C, 385°C, and 559°C and three reduction peaks at 250°C, 380°C, 584°C for Ni/5La–ZrO 2 catalyst corresponding probably to NiO nanocrystals of various sizes 36 .…”
Section: Resultsmentioning
confidence: 97%
“…NiFe/Al 2 O 3 showed three reduction peaks at 396, 476, and 681 °C. The first and second peaks were assigned to noninteracting and weakly interacting nickel oxide, respectively, while the third peak was assigned to the reduction of NiO associated with Al 2 O 3 . , In addition, NiFe/ZrO 2 showed a main peak at 369 °C, and NiFe/CeO 2 showed two peaks at 330 and 382 °C, which were attributed to the reduction of nickel oxide. , …”
Section: Resultsmentioning
confidence: 99%
“…40,41 In addition, NiFe/ZrO 2 showed a main peak at 369 °C, and NiFe/CeO 2 showed two peaks at 330 and 382 °C, which were attributed to the reduction of nickel oxide. 42,43 TEM images and metal particle size distribution of NiFe/ SBA-15 are shown in Figure 3(a) and (b). The uniform channel structure of SBA-15 and a uniform dispersion of NiFe bimetallic particles on the support were observed.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The transformation of biomass‐derived substrates into value‐added platform chemicals and fuels has been drastically increased during the past few decades, because it has been forecasted that limited fossil resources will steadily diminish as the global population is estimated to increase to approximately 11 billion by end of this century . Fossil resources are being predominantly utilized for the production of primary energy and commodity chemicals for fulfilling the basic needs of society .…”
Section: Introductionmentioning
confidence: 99%